(untitled) (Research, Society and Development, 2021)
Obtaining safe and quality food is the fundamental requirement of the consumer at the time of purchase. Food safety is gaining prominence day after day, and the responsibility to offer innocuous food is a function of all links in the production chain, including the packaging sector and the equipment that comes into contact with the food. The present work aimed to carry out a survey of data and information on food contamination due to the migration of components of packaging and equipment, and to analyze the reasons that have caused this migration. The work presented a qualitative approach, based on a bibliographic search on articles and publications of the packaging legislation. From the analysis of seven reports presented, it was observed that one of the reasons that has stood out in causing the migration of compounds for food is the negligence in the use of these materials by packaging manufacturers and consumers. Therefore, it can be considered that the packaging and food equipment sectors need to seek a balance in the following points: to improve the compatibility between material and food, to control factors such as storage and contact time, to bring complete information to the consumer through the labels and to advise on instructions for use for each type of material. A combination of all these factors together with an adequate inspection by Organs responsible agencies will inhibit reducing the cases of food contamination by migration of compounds harmful to health.